TEACHING METHODS AND PSYCHOLOGICAL-EDUCATIONAL TECHNOLOGIES: ESSENCE, DEVELOPMENT TRENDS - Dilbar Negmatovna Alimdjanova; Doniyor Vakhobjonovich Berdiev; Gulirano Vahobjonovna Berdieva (International Journal on Integrated Education, 2023)
The article discusses significant concepts: “teaching”, “teaching methods”, “technology”; an attempt is also made to define the concepts of pedagogical technology, learning technology, psychological-pedagogical technology, their relationship and interaction. The substantive characteristics of these and other concepts are updated (manifested) and gradually improved in psychological and pedagogical activities. In addition, various classifications of teaching methods and types of technologies are analyzed.